JUPITER: ZONAL SPECTROPHOTOMETRY OF WEAK AMMONIA ABSORPTION BANDS IN 2018 - V.G. Teifel; P.G. Lysenko; A.M. Karimov; G.A. Kirienko; V.A. Filippov; G.A. Kharitonova; A.P. Hozhenets (Academic Scientific Journal of Computer Science, 2019)
Based on measurements of zonal spectrograms obtained by scanning the Jupiter disk in March – June 2018, the profiles of the 645 and 787 nm weak absorption bands of NH3, and the character of the zonal absorption variations at different latitudes are derived. A standard has been prepared for processing and analyzing data in relation to further studies of possible seasonal and sporadic variations based on Jupiter’s spectral observations for the full period of its rotation around the Sun. The zonal and latitudinal variations of ammonia absorption are shown. As in previous years, the NH3 absorption depression is particularly prominent at the latitude of about + 150 in the NEB region. As in previous years, some differences in the latitudinal absorption of the 645 and 787 nm NH3 bands remain.